Influence of Oxidative Stress on Biocontrol Activity of Cryptococcus laurentii against Blue Mold on Peach Fruit - Zhang, Zhanquan; Chen, Jian; Li, Boqiang; He, Chang; Chen, Yong; Tian, Shiping (Frontiers in Microbiology, 2017)
The limitations of chemical fungicides for the control postharvest diseases have recently become more apparent. The utilization of antagonistic microorganisms is a promising alternative to that of fungicides to control postharvest decay. In previous studies, the antagonistic yeast Cryptococcus laurentii has shown excellent effects of biocontrol and great potential for practical application. Adverse conditions, such as oxidative stress, limit the practical application of antagonistic yeast. In this study, we investigated the oxidative stress tolerance of C. laurentii and the associated mechanisms. The results indicated that exogenous oxidative stress has a significant effect on the viability and biocontrol efficiency of C. laurentii. H2O2-induced oxidative stress led to the accumulation of reactive oxygen species. The results of flow cytometric analysis suggested that apoptosis is responsible for the reduced survival rate of C. laurentii under oxidative stress. Using tests of antioxidant activity, we found that C. laurentii could employ enzymatic systems to resist exogenous oxidative stress. The addition of exogenous glutathione, a non-enzymatic antioxidant, to the media can significantly enhance oxidative tolerance and biocontrol efficiency of C. laurentii.